Polyvinyl Alcohol – Sodium Nitrite Water Soluble Composite as a Corrosion Inhibitor for Mild Steel in Simulated Cooling Water - S. Yaro, Aprael; M. Darweesh, Teeba (Iraqi Journal of Chemical and Petroleum Engineering, 2012)
The inhibitive action of polyvinyl alcohol –sodium nitrite (PVASN) composite on the corrosion of mild steel in simulated cooling water (SCW) has been investigated by weight loss and potentiodynamic polarization. The effect of composite concentration (PVA/SN) , pH, and exposure time on corrosion rate of mild steel were verified using 2 levels factorial design and surface response analysis through weight loss approach, while the electrochemical measurements were used to study the behavior of mild steel in (SCW) with pH between 6 and 8 and in absence and presence of (PVA) in solution containing different concentration of NaNO2. It was verified that all three main variables studied were statistically significant while their interaction is less pronounced.